2008
DOI: 10.1016/j.ab.2007.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Saturation fluorescence labeling of proteins for proteomic analyses

Abstract: We present here an optimized and cost-effective approach to saturation fluorescence labeling of protein thiols for proteomic analysis. We investigated a number of conditions and reagent concentrations including a disulfide reducing agent (TCEP), pH, incubation time, linearity of labeling, and saturating dye: protein thiol ratio with protein standards to gauge specific and nonspecific labeling. Efficacy of labeling under these conditions was quantified using specific fluorescence estimation, defined as the rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 19 publications
1
48
0
Order By: Relevance
“…Focusing on thiols also allows the pIs of labeled proteins to be maintained since the dyes are neutrally charged. Recently, it has been demonstrated that saturation labeling of thiols can also be successfully carried out using the BODIPY dyes (FL-N-(2-aminoethyl) maleimide; FL C1-idoacetamide) by optimizing the labeling reaction conditions [148]. The BODIPY dyes demonstrate a LLD of 10 fmol (without a reported error) and a LDR of three orders of magnitude for yeast enolase I. Inter-protein variation was not referred to but can be inferred from the thiol specific nature of these dyes [148].…”
Section: Reactive Fluorescent Dyesmentioning
confidence: 99%
“…Focusing on thiols also allows the pIs of labeled proteins to be maintained since the dyes are neutrally charged. Recently, it has been demonstrated that saturation labeling of thiols can also be successfully carried out using the BODIPY dyes (FL-N-(2-aminoethyl) maleimide; FL C1-idoacetamide) by optimizing the labeling reaction conditions [148]. The BODIPY dyes demonstrate a LLD of 10 fmol (without a reported error) and a LDR of three orders of magnitude for yeast enolase I. Inter-protein variation was not referred to but can be inferred from the thiol specific nature of these dyes [148].…”
Section: Reactive Fluorescent Dyesmentioning
confidence: 99%
“…A549 nuclear protein was labeled with BODIPY (Invitrogen) before IEF/ 2-DE according to our previously published protocol (23). To label proteins, 150 to 200 g protein were denatured in 200 l of reaction buffer (50 mM Tris-HCl [pH 7.5], 7 M urea, 2 M thiourea, 2% CHAPS) and incubated with 60-fold excess BODIPY over protein thiols for 2 h at 22°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, the nuclear proteins that are protected are unknown. To determine their identities, we adapted a sensitive cysteinyl-reactive saturation fluorescence labeling technique to identify proteins that are oxidized in response to RSV in the presence or absence of Prdx knockdown (23). This technique uses BODIPY to covalently label protein cysteines when they are reduced.…”
Section: Identification Of Proteins Protected By Prdx-1 and Prdx-4 Frmentioning
confidence: 99%
“…However, IAM is more selective for the thiolate anion and results in lower nonspecific labeling compared with NEM, making IAM-DES a highly specific and selective labeling reagent for the reactive thiols generated after Grx1 reduction. IAM requires a more alkaline pH range (7.5-8.5) for optimum reactivity and reacts more readily with cysteines at their pKa around pH 8.0 (46,71). At higher pH values and temperatures, IAM can alkylate methionines, lysines, arginines, tyrosines, histidines, and the N-terminal and Cterminal carboxyl (20,35,70).…”
Section: Labeling Of S-glutathionylated Proteinsmentioning
confidence: 99%
“…NEM was added prelysis to avoid thiol oxidation during cell lysis and other processing steps and to avoid loss of protein thiol-GSH mixed disulfides due to transthiolation and disulfide formation during sample preparation (18). NEM is a commonly used thiol-alkylating agent because of its high reactivity and specificity for thiols at physiological pH (6.5-7.5); at higher pH (>7.5), NEM reacts with lysines, arginines, histidines, and tyrosines (37,46) and has been reported to also react with sulfenic acids (49) and possibly with sulfinic acids (29,49). NEM has proven to be a better overall alkylating agent than IAM based on its ability to react with free thiols and sulfenic acids faster, more efficiently, and within a broader effective pH range (49,51).…”
Section: Labeling Of S-glutathionylated Proteinsmentioning
confidence: 99%